Hypercalcemia and Bone Metastasis in a Case of Large Cell Neuroendocrine Carcinoma With Unknown Primary - Ekrem Yetiskul; Jordyn Salak; Fatema Arafa; Alaukika Agarwal; Amanda Matra; Muhammad Niazi; Marcel Odaimi (Case Reports in Oncological Medicine)
Large cell neuroendocrine carcinoma (LCNEC) constitutes a rare subset of highly undifferentiated malignancies known for their aggressive nature. Although these tumors commonly originate in the lungs and gastrointestinal tract, their potential occurrence is not restricted to specific anatomical sites, giving rise to a variety of symptoms. Notably, cases of neuroendocrine tumors (NETs) with an unidentified primary source exhibit a graver prognosis and shorter survival periods compared to those with clearly identified origins. NETs frequently demonstrate a propensity to metastasize, spreading to diverse anatomical regions such as the liver, lungs, lymph nodes, and bones, illustrating their aggressive nature and the complexity of their management. In this context, we present the case of a 59-year-old male who sought medical attention in the emergency department due to right upper quadrant (RUQ) abdominal pain. Initial diagnostic assessments revealed significantly elevated liver function tests and severe hypercalcemia. A right upper quadrant ultrasound (RUQ US) was subsequently performed, which revealed heterogeneous hepatic echotexture with innumerable echogenic masses, suggesting a metastatic process. A computed tomography (CT) scan was then ordered to evaluate further the RUQ US findings, which showed numerous hypovascular liver masses, raising concerns of malignancy. A liver biopsy confirmed a diagnosis of LCNEC with an unidentified primary source.